The Upaya Kementerian Agama Kota Medan dalam Menyuluh Masyarakat Muslim terhadap Urgensi Konsumsi Produk Halal - Fandhy, Arya; Robino, Robino (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2023)
The heterogeneity of communities in their social activities does not always have a positive impact on the Muslim community in the field, because such heterogenous associations can cause some Muslim communities to lose consciousness in consuming non-halal products. Therefore, in such a situation, it is important for the Ministry of Religion to inform the public about the importance of consuming halal products, raising awareness, empowering consumers, establishing cooperation with the local government and related agencies, as well as strengthening the certification and monitoring system. This research uses a qualitative descriptive approach to the type of phenomenological research. Primary data in this study is information and phenomena obtained directly, while secondary data on this study covers relevant documents and literature. The data collection in this study included semi-structured interviews and non-participant observations. The data verification technique in this study uses triangulation techniques. The results of this study showed that the Ministry of Religion of the City of Medan carried out comprehensive communication efforts to alert the Muslim community to the urgency of consuming halal products. The Ministry’s efforts include dissemination, halal certification, social media campaigns, cooperation with industry and trade, supervision, law enforcement, as well as collectivity through communication within social groups.